2019
DOI: 10.1242/dev.179663
|View full text |Cite
|
Sign up to set email alerts
|

The simultaneous interaction of MSL2 with CLAMP and DNA provides redundancy in the initiation of dosage compensation in Drosophila males

Abstract: The binding of the Drosophila male-specific lethal dosage compensation complex (DCC) exclusively to the male X chromosome provides an excellent model system to understand mechanisms of selective recruitment of protein complexes to chromatin. Previous studies showed that the male-specific organizer of the complex, MSL2, and the ubiquitous DNA-binding protein CLAMP are key players in the specificity of X chromosome binding. The CXC domain of MSL2 binds to genomic sites of DCC recruitment in vitro. Another conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(60 citation statements)
references
References 35 publications
2
58
0
Order By: Relevance
“…MSL2 contributes to the specific recognition of HASs through the direct binding of GAGA motifs (23) andinteractions with CLAMP(28,29). However, our results suggested that the protein-protein interactions mediated by the N-terminal domain of MSL1 are the most critical interactions that define the specific binding of MSL to the X chromosome.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…MSL2 contributes to the specific recognition of HASs through the direct binding of GAGA motifs (23) andinteractions with CLAMP(28,29). However, our results suggested that the protein-protein interactions mediated by the N-terminal domain of MSL1 are the most critical interactions that define the specific binding of MSL to the X chromosome.…”
mentioning
confidence: 84%
“…This model was based on the finding that the ectopic expression of the MSL2 protein in females induced the formation of the DCC on the X chromosome. In a previous study (29), we showed that MSL1 and MSL2 were specifically recruited to the X chromosome in transgenic females expressing MSL2 WT -3xFLAG under the control of the Ubi promoter (86Fb). Even heterozygous MSL2 wt /+ females displayed reduced viability relative to males.…”
Section: N-terminal Sequences Of Msl1 Are Critical For the Specific Rmentioning
confidence: 95%
See 3 more Smart Citations